A brightly emissive halomanganates(II) with triphenylphosphonium cation: Synthesis, luminescence, and up-conversion phenomena. (December 2021) - Berezin, Alexey S.
Abstract: A series of [HL]2 [MnX4 ] [X = I, Br, Cl] tetrahalomanganates with triphenylphosphonium cation has been designed and investigated in photophysics and EPR terms. At room temperature, the solid complexes exhibit a remarkably bright green phosphorescence ( λ max  = 525 nm–555 nm) resulted from the Mn(II) d - d transitions ( 4 T1 → 6 A1 ) with high quantum efficiency (>50%) and a short lifetime of the iodomanganate complex (≈41 μs). Under infrared excitation (λEx  = 780 nm) the complexes exhibit unusually luminescence in the visible region ( λ max  ≈ 500 nm). The EPR spectra of complexes are characterized by the deviation of the g -factor from the g e free electron value and by the high value of the zero-field splitting parameters on account of the spin-orbit coupling. The correlations between the luminescence and magnetic properties of the title complexes are discussed. Highlights: A novel halomanganetes(II) with high efficiency of phosphorescence are reported. Halide-depending crystal field splitting and Racah parameters. Halomanganetes(II) exhibiting the up-conversion luminescence. Metal-to-ligand charge transfer in manganese(II) compounds. Potential energy surface of ground and excited states.